Bayesian Revision of the Folsom Age Range Using IntCal20. (3rd April 2021) - Buchanan, Briggs; David Kilby, J.; Hamilton, Marcus J.; LaBelle, Jason M.; Meyer, Kelton A.; Holland-Lulewicz, Jacob; Andrews, Brian; Morgan, Brooke M.; Asher, Brendon; Holliday, Vance T.; Hodgins, Gregory W. L.; Surovell, Todd A.
ABSTRACT: Folsom is an early Paleoindian archaeological tradition found in the North American West. Here we report new AMS radiocarbon dates for the Barger Gulch and Lindenmeier sites in Colorado along with unsuccessful dating attempts for Blackwater Draw, the Mitchell Locality, Shifting Sands, and Lipscomb on the Southern Plains. We applied Bayesian modeling using IntCal20 to our updated set of Folsom dates and estimate that the Folsom tradition lasted for a period spanning between 355–510 years at the 68 per cent credible interval or 325–650 years at the 95 per cent credible interval, starting sometime between 12, 845–12, 770 calendar years ago (cal yr BP) and ending sometime between 12, 400–12, 255 cal yr BP. Additionally, we model the spans of the start and end boundaries and find that both the adoption and abandonment of Folsom technology occurred over relatively short periods, less than 100 years and likely less than 50 years.